Model output for the paper "Reconciling the conflicting extent of overriding plate deformation before and during megathrust earthquakes in South America, Sunda, and northeast Japan" - D'Acquisto, Mario (Utrecht University, 2022)
This repository contains the relevant data (part of numerical model output) used to plot the figures in the main body of the manuscript mentioned in the title, authored by Mario D’Acquisto, Taco Broerse, Celine P. Marsman, and Rob Govers, submitted for publication in Geophysical Journal International.

Paper abstract: "We aim to better understand the overriding plate deformation during the megathrust earthquake cycle. We estimate the spatial patterns of interseismic GNSS velocities in South America, Southeast Asia, and northern Japan and the associated uncertainties due to data gaps and velocity uncertainties. The interseismic velocities with respect to the overriding plate generally decrease with distance from the trench with a steep gradient up to a “hurdle”, beyond which the gradient is distinctly lower and velocities are small. The hurdle is located 500–1000 km away from the trench, for the trench-perpendicular velocity component, and either at the same distance or closer for the trench-parallel component. Significant coseismic displacements were observed beyond these hurdles during the 2010 Maule, 2004 Sumatra-Andaman, and 2011 Tohoku earthquakes. We hypothesize that both the interseismic hurdle and the coseismic response result from a mechanical contrast in the overriding plate. We test our hypothesis using physically consistent, generic, three-dimensional finite element models of the earthquake cycle. Our models show a response similar to the interseismic and coseismic observations for a compliant near-trench overriding plate and an at least 5 times stiffer overriding plate beyond the contrast. The model results suggest that hurdles are more prominently expressed in observations near strongly locked megathrusts. Previous studies inferred major tectonic or geological boundaries and seismological contrasts located close to the observed hurdles in the studied overriding plates. The compliance contrast probably results from thermal, compositional and thickness contrasts and might cause the observed focusing of smaller-scale deformation like backthrusting."

The software used to perform the simulations, extract the model output in the files stored here, and perform additional processing for the plotting of figures was GTECTON (Govers & Wortel, 1993, 2005; Govers et al., 2018), version 2021.0. The software used to plot the relevant figures in the paper from the data was Generic Mapping Tools (GMT) (Wessel et al., 2019) version 6.3.0.

Please refer to readme.txt and the paper for more information about the content of the repsitory and the methods and results of the modeling, respectively.

Contact person: Mario D'Acquisto - m.dacquisto@uu.nl
Keywords: Natural Sciences - Earth and related environmental sciences (1.5); numerical modeling; megathrust; earthquake cycle; interseismic; surface velocity; coseismic; surface displacement; geophysics; tectonics; satellite geodesy